Meta-Analysis of early childhood learning during the Covid-19 Pandemic using the prism method - Muji, Anggarda Paramita; Jamaris, Jamaris; Solfema, Solfema; Hidayat, Hendra (Universitas Negeri Padang, 2022)
In the current Covid-19 transition period, innovations in early childhood learning models are needed that are effectively used. The many models of early childhood learning during this pandemic need to be studied further which are appropriate for implementation. This study aims to empirically verify the early childhood learning model during the COVID-19 pandemic and analyze the factors that influence early childhood learning during the Covid-19 period. The method used in writing this article is a systematic literature review, which is a literature search from national article sources conducted using indexed searches on Google Scholar and Microsoft Academic. This literature review was conducted using the prism method technique. The articles reviewed are the most recent 50 articles from 2020 to 2021, and the results were sorted into 26 articles. All articles are classified by year of publication, type of indexing journal, method, and early childhood learning model. The results of the study are presented as follows. (1) The search results prove an increase in the number of articles published from 2020-2021. (2) The results of the study show that the most widely used learning model in early childhood learning involves the participation and assistance of parents in children's learning at home through learning media created by teachers and distributed through social media. (3) The obstacles that can be identified are: (a) the role of parents in children's learning during the pandemic is still less than optimal, (b) the lack of mastery of technology skills of students and parents during online learning. So it is necessary to develop an early childhood learning model that can be applied in online implementation, able to facilitate collaboration between parents, teachers, and students.